Physical activity, hormone replacement therapy and breast cancer risk: A meta-analysis of prospective studies. (January 2016) - Pizot, Cécile; Boniol, Mathieu; Mullie, Patrick; Koechlin, Alice; Boniol, Magali; Boyle, Peter; Autier, Philippe
Abstract: Background: Lower risk of breast cancer has been reported among physically active women, but the risk in women using hormone replacement therapy (HRT) appears to be higher. We quantified the association between physical activity and breast cancer, and we examined the influence that HRT use and other risk factors had on this association. Methods: After a systematic literature search, prospective studies were meta-analysed using random-effect models applied on highest versus lowest level of physical activity. Dose–response analyses were conducted with studies reporting physical activity either in hours per week or in hours of metabolic equivalent per week (MET-h/week). Results: The literature search identified 38 independent prospective studies published between 1987 and 2014 that included 116, 304 breast cancer cases. Compared to the lowest level of physical activity, the highest level was associated with a summary relative risk (SRR) of 0.88 (95% confidence interval [CI] 0.85, 0.90) for all breast cancer, 0.89 (95% CI 0.83, 0.95) for ER+/PR+ breast cancer and 0.80 (95% CI 0.69, 0.92) for ER−/PR− breast cancer. Risk reductions were not influenced by the type of physical activity (occupational or non-occupational), adiposity, and menopausal status. Risk reductions increased with increasing amounts of physical activity without threshold effect. In six studies, the SRR was 0.78 (95% CI 0.70, 0.87) in women who never used HRT and 0.97 (95% CI 0.88, 1.07) in women who ever used HRT, without heterogeneity in results. Findings indicate that a physically inactive women engaging in at least 150 min per week of vigorous physical activity would reduce their lifetime risk of breast cancer by 9%, a reduction that might be two times greater in women who never used HRT. Conclusion: Increasing physical activity is associated with meaningful reductions in the risk of breast cancer, but in women who ever used HRT, the preventative effect of physical activity seems to be cancelled out. Highlights: Increasing physical activity is associated with meaningful reductions in the risk of breast cancer. Risk reductions associated with physical activity are independent from adiposity and menopausal status. Risk reductions seem more pronounced for cancers that are oestrogen–progesterone receptor negative. The preventative effect of physical activity seems to be cancelled out in women who ever used hormone replacement therapy.